Dilution of Highly Concentrated LiBF4/Propylene Carbonate Electrolyte Solution with Fluoroalkyl Ethers for 5-V LiNi0.5Mn1.5O4 Positive Electrodes. Issue 1 (1st January 2017) - Doi, Takayuki; Shimizu, Yusuke; Hashinokuchi, Michihiro; Inaba, Minoru
Abstract : Various kinds of fluoroalkyl ethers were investigated as diluents to reduce the high viscosity of highly concentrated LiBF4 /PC electrolyte solutions. 1, 1, 2, 2–tetrafluoroethyl 2, 2, 3, 3–tetrafluoropropyl ether (HFE) was the most suitable diluent because of a high solubility of LiBF4 . 2.50 mol kg −1 LiBF4 /PC+HFE (2:1 by volume) was a reasonable compromise to attain a low viscosity (51.7 mPa s) and a low PC/Li molar ratio (2.39). Raman spectroscopy revealed that the fraction of free PC molecules in 2.50 mol kg −1 LiBF4 /PC+HFE (2:1) was much smaller than 2.50 mol kg −1 LiBF4 /PC (PC/Li molar ratio = 4.00), and that the interactions of HFE with Li + cations and BF4 − anions were very weak. LiNi0.5 Mn1.5 O4 positive electrodes showed high charge/discharge performance with low irreversible capacities in 2.50 mol kg −1 LiBF4 /PC+HFE (2:1), which showed that the highly concentrated LiBF4 /PC system can be diluted with HFE without losing the high stability against oxidation.